Spatial distribution characteristics, source analysis and risk assessment of polycyclic aromatic hydrocarbons in topsoil of a typical chemical industry park - Zhang, Yongjiang; Niu, Jiawei; Wei, Zejun; Zhou, Xunping; Wu, Lijun; Li, Xixi; Ma, Shuang; Shi, Ge (Frontiers in Environmental Science, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are widely distributed in soil and are difficult to degrade, posing a great threat to the ecological environment and human health. Therefore, research on the distribution characteristics and risks of PAHs is of great significance to protect human and ecosystem health. Taking a typical chemical industry park in Chongqing as an example, the spatial distribution characteristics of PAHs content in 54 topsoil samples in the typical area were analyzed, and the soil PAHs pollution was evaluated by incremental models such as single-factor index and Nemerow comprehensive index. A factor decomposition model Positive Definite Matrix Factorization (PMF) was used to analyze the sources of PAHs. The results showed that 16 kinds of optimally controlled PAHs were detected, and the content of ΣPAHs in the topsoil ranged from ND to 16.07 mg/kg, with an average value of 1.78 mg/kg; spatially, pollutant levels are higher in the south and southwest of the park as well as in the center; source analysis showed that Chongqing The PAHs pollution in this typical chemical industry park in the city is from coke combustion sources, traffic emission sources, biomass combustion sources, oil sources, coal combustion sources and oil leakage sources, and the contribution rates to PAHs are 10.7%, 35.2%, 20.7%, and 5.0%, 24.6% and 3.7%; respectively. the health risk assessment of soil PAHs shows that there is no potential carcinogenic risk of PAHs in different age groups in this area, and the main exposure route of adults is dermal> ingestion> inhalation, and the main exposure route of children is ingestion> dermal> inhalation.